PROJECTION OF THE 7Liαt WAVE FUNCTION ON THE 5Неαn+d CLUSTER CHANNEL. I ELEMENTS OF THE FORMALISM - Afanasyeva, N.V.; Burkova, N.A.; Zhaksybekova, K.A. (Recent Contributions to Physics, 2017)
Within the at-model for 7Li nucleus 5He+d relative motion wave functions have been built by using the projecting method, also the analytical expression for spectroscopic Sd -factors of deuterons separation has been obtained.